An ad for success: a case study exploring one woman’s higher education and professional paths that led her to leadership in creative departments dominated by men - Olsen, Katie Rose (Kansas State University, 2018)
The purpose of this study was to explore how one woman negotiated an educational and professional path that led to leadership within the advertising industry’s creative departments, where most of the leadership positions are held by men. This qualitative study was conducted using purposeful sampling, as the single participant represented a truly unique situation in that she held the title of Executive Creative Director at a top advertising agency by the age of 33. Through The 3% Movement, it was identified that less than 12% of advertising’s creative directors are women (2017), and it was this stark gender gap that served as the impetus for exploring this woman’s experiences. A case study design was used to explore her experiences throughout childhood, higher education, professional school, and finally as a professional, in order to understand her path in a deep and meaningful manner. The theoretical framework for this study was based on a feminist perspective using social role theory (Eagly, 1997). A participant-created childhood timeline, three in-depth interviews, two writing responses, and a photo and object elicitation session served as the primary sources of data. The data were analyzed and coded using in-vivo and descriptive coding, as well as pattern-finding, over two cycles of coding and analysis (Saldaña, 2016). The data were used to answer the study’s two overarching research questions, and the following three themes were identified: 1) the power of a woman’s influence; 2) developing passion for leadership and creativity; and 3) promoting a strong work-life balance. The findings indicate that women must have support systems in place in order to successfully manage life as mothers and creative directors. Recognizing one’s own leadership and creative skills, and constantly working to provide the best team environment, were also recognized as key to moving forward in leadership positions within advertising’s creative departments. Agencies must establish policies and procedures to support both men and women as they manage a work-life balance, and it is even more important for leaders to set a positive example for those working around them. Finally, educating everyone holding authority within creative departments about the gender gap can increase awareness and provide the knowledge needed to support women. The findings of this study have implications for a variety of entities impacting women and their creative careers, from faculty and those involved with co-curricular activities in both high school and in higher education, those pursuing post-graduate advertising portfolio school, and those creative directors and agencies that do not reflect the goals of The 3% Movement in reducing the gender gap. Recommendations for future research include additional case studies exploring women creative directors and their paths to leadership, analyses of agencies’ policies and procedures impacting women, promotional processes of advertising’s creative departments, and further cross-case analyses of both women creative directors and various agencies representing different stages of diversity within the creative departments.
Keywords: Advertising; Gender gap; Social role theory; FeminismHigher education